2015
DOI: 10.1063/1.4914883
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polarization relaxation in Au/Cu2O/ZnO/BiFeO3/Pt heterostructure

Abstract: The stability of polarization in ferroelectric BiFeO3 thin film stacked with a p-n junction of Cu2O/ZnO was studied in the Au/Cu2O/ZnO/BiFeO3/Pt heterostructure. It was observed that the downward ferroelectric polarization of BiFeO3 gradually relaxes once the external electric field is removed, which is driven by the depolarization effect induced by the reduction of compensating charges due to the charge redistribution within Cu2O/ZnO. This work contributes to an improved understanding on the polarization beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…thought that the biased coercive field of Si-doped HfO 2 on the p-Si substrate was caused by the depolarization field, counteracted by the charge trapping at the interface . Fan et al believed that the decrease in the compensation charge at the interface was the main reason for the polarization relaxation of BiFeO 3 (BFO) on the ZnO substrate, while through molecular dynamics simulation, Zhu et al showed that the aggregation of oxygen vacancies at the interface could significantly reduce the ferroelectric polarization . Some other works focus on the electrical transport in the ferroelectric/semiconductor heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…thought that the biased coercive field of Si-doped HfO 2 on the p-Si substrate was caused by the depolarization field, counteracted by the charge trapping at the interface . Fan et al believed that the decrease in the compensation charge at the interface was the main reason for the polarization relaxation of BiFeO 3 (BFO) on the ZnO substrate, while through molecular dynamics simulation, Zhu et al showed that the aggregation of oxygen vacancies at the interface could significantly reduce the ferroelectric polarization . Some other works focus on the electrical transport in the ferroelectric/semiconductor heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the BZT/PZT/BZT/LNO thin film, the leakage current exhibits an unsymmetrical characteristic, which is higher at positive bias voltages. A possible reason may be the asymmetric electrodes that lead to different interfacial Schottky barrier heights and induce the unsymmetrical characteristics of IV curve (Shen et al, 2014;Fan et al, 2015;Chen et al, 2020). To further study the effects of the LNO seed layer on the polarization behavior of thin films, piezoelectric force microscopy (PFM) was employed to directly observe the polarization reversal behavior, based on the evolution of piezoelectric response.…”
Section: Resultsmentioning
confidence: 99%
“…The Edp is often blamed for the instability of ferroelectric polarization 174,175 and even the disappearance of ferroelectricity in ultrathin films with the thickness below a few nanometers. The magnitude of Edp is negligible in bulk ferroelectrics because the distance between the two charged surfaces is very large.…”
Section: Depolarization Field Driven Photovoltaic Effectmentioning
confidence: 99%
“…However, in ferroelectric thin lms, the lm thickness is usually below a few hundreds of nanometers and therefore the effect of E dp can be signicant. The E dp is oen blamed for the instability of ferroelectric polarization 174,175 and even the disappearance of ferroelectricity in ultrathin lms with the thickness below a few nanometers. 176 Therefore, ferroelectric polarization in thin lms can only become stable when the polarization charges are screened by the charge carriers from ferroelectrics themselves or from electrodes.…”
Section: Photovoltaic Mechanismsmentioning
confidence: 99%